P174 Initial process evaluation findings from the at-risk registers integrated into primary care to stop asthma crises in the UK (ARRISA-UK) trial: practice characteristics, engagement and early experiences of the intervention. (12th November 2019) - Smith, JR; Noble, MJ; Winder, R; Poltawski, L; Ashford, PA; Musgrave, S; Stirling, S; Morgan-Trimmer, S; Caress, AL; Wilson, AM
Abstract : Introduction: The ARRISA-UK trial is investigating whether, compared to usual care, a GP practice-level complex intervention decreases the proportion of 'at-risk' asthma patients who experience asthma-related A&E attendances, hospitalisations or death over 12 months. This presentation reports initial findings from a nested process evaluation. Methods: ARRISA-UK is a nationwide cluster-randomised controlled trial of an intervention involving identification and flagging of at-risk asthma patients' electronic records and web-based training of practice staff to support implementation of actions in response to the flags (e.g. improved access and opportunistic care). A mixed-methods process evaluation is exploring intervention implementation, mechanisms of action and the influence of contextual factors (e.g. practice characteristics). Quantitative and qualitative data from questionnaires, training software, practice-specific action plans and staff focus groups/interviews were analysed to describe practice characteristics, and their engagement with, and initial implementation and experiences of, the ARRISA-UK approach. Results: The 275 recruited practices, from across 14 English Clinical Research Network Regions, 7 Welsh and 5 Scottish Health Boards, had a median list size of 8801 (range 1667–37800) and identified 10, 000+ at-risk asthma patients in total, representing an average of 33 (range 1–197) and 6% (range 0.2–13%) of registered asthma patients per practice. There was considerable variation in the characteristics of the 139 intervention practices (Table 1). Despite some early documented difficulties with technology and staff turnover, at least 409 staff (GPs, nurses, receptionists/administrators, dispensers/pharmacists) from 131 (94%) practices completed at least minimum individual on-line training, reflecting a median of 3 (maximum of 9) staff per practice. 128 (92%) practices also completed group training to prepare Action Plans, attended a webinar and activated flagging. Action plans varied in content and detail but illustrated ways for staff to enhance access to, and uptake of, asthma-related services by at-risk patients. Questionnaires suggested the training was generally well-received. Analyses of staff focus groups/interviews are underway. Conclusions: The ARRISA-UK intervention represents a pragmatic, practice-wide approach to targeting at-risk asthma patients which has been successfully implemented across a variety of GP practices and generally engaged and been well-received by all practice staff groups. Initial findings have informed ongoing quantitative and qualitative data collection.